2022
DOI: 10.3390/ma15020461
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Impedance of Surface Modified Porous Titanium Implants with Femtosecond Laser

Abstract: The chemical composition and surface topography of titanium implants are essential to improve implant osseointegration. The present work studies a non-invasive alternative of electrical impedance spectroscopy for the characterization of the macroporosity inherent to the manufacturing process and the effect of the surface treatment with femtosecond laser of titanium discs. Osteoblasts cell culture growths on the titanium surfaces of the laser-treated discs were also studied with this method. The measurements ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…It was also observed, among other things, in the potentiodynamic polarization curves. Navarro [26] showed that a femtosecond laser modification caused changes in the surface of modified samples with different porosities, resulting in an increased impedance (Figure 5). Tests carried out by [103,104] indicated that a thicker oxide or nitride layer formed after laser modification on a material surface, improved the corrosion resistance of a titanium alloy.…”
Section: Corrosionmentioning
confidence: 99%
“…It was also observed, among other things, in the potentiodynamic polarization curves. Navarro [26] showed that a femtosecond laser modification caused changes in the surface of modified samples with different porosities, resulting in an increased impedance (Figure 5). Tests carried out by [103,104] indicated that a thicker oxide or nitride layer formed after laser modification on a material surface, improved the corrosion resistance of a titanium alloy.…”
Section: Corrosionmentioning
confidence: 99%
“…In modern implantology, titanium and its alloys are commonly used as materials for fabrication of dental implants and joint replacements [1]. Titanium became a preferred substrate among other materials because of the combination of its outstanding biocompatible properties, corrosion resistance, high load-bearing capacity, rigidity, and lightness [2]. Factors such as type and design of material, surface properties or the quality and volume of the host bone affect biocompatibility [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the surface hardness often acts as a limitation on the applications of Ti-6Al-4V [3]. Applications for Ti alloy surface modification have been reported to improve the behavior of Ti implants, such as the creation of surface nanostructures to improve the osseointegration process [4,5]. On the other hand, surface modification is also an important approach to strengthen the surface of Ti alloys.…”
Section: Introductionmentioning
confidence: 99%